فعالية بيئة اللغوية لترقية مهارة الكلام: Efektivitas Lingkungan Bahasa untuk Meningkatkan Keterampilan Berbicara - Luthfi, Ibnu Mas'ud (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2025)
This study aims to evaluate the effectiveness of using a language environment in improving students' speaking skills. A language environment refers to a learning environment that encourages students to communicate using the target language in various activities, both inside and outside the classroom. This study used a quasi-experimental method with a pretest and posttest design on two groups: an experimental group treated with the language environment, and a control group treated with a conventional learning approach. Data were collected through oral tests, observation, and documentation. The results showed a significant difference in speaking skill improvement between the two groups. Students learning in a language environment showed greater improvement in fluency, pronunciation, and speaking confidence. Thus, using a language environment can be considered an effective approach to teaching speaking skills.